Computer Science Stack Exchange is a question and answer site for students, researchers and practitioners of computer science. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Do anyone have any idea how to solve this recurrence?$$T(k) = \sum_{i=1}^{k/2} {k \choose i}T(i)T(k-i)$$

I am working with this kind of recurrence for the first time and don't have much idea of how to proceed. But, for beginning I was trying to guess the solution and use substitution method. But, in the guessing part itself I am stuck. It seems like the solution should be exponential to $k$.

share|cite|improve this question
up vote 6 down vote accepted

Everything becomes much simpler if when $n$ is odd we stop the sum at $\lfloor n/2 \rfloor$, and when $k$ is even we discount the term corresponding to $k/2$ by a half. In that case you can write $$ 2T(k) = \sum_{i=1}^{k-1} \binom{k}{i} T(i) T(k-i) $$ and so, putting $T(0) = 0$, we get that for $k \geq 2$, $$ 2T(k) = \sum_{i=0}^k \binom{k}{i} T(i) T(k-i). \tag{1}$$ (When $k = 1$ this reads $2T(1) = 0$.)

Now define the exponential generating function $$ P = \sum_{n \geq 0} T(n) \frac{x^n}{n!}. $$ Put $T(1) = c$. The identity (1) implies the equation $$ 2(P-cx) = P^2. $$ Solving the quadratic, we obtain $$ P = 1 - \sqrt{1 - 2cx} = 1 - \sum_{n \geq 0} \frac{(2n)!}{(1-2n)(n!)^24^n} (2cx)^n = \sum_{n \geq 1} \frac{(2n)!(c/2)^n}{(2n-1)n!} \frac{x^n}{n!}. $$ We conclude that for $n \geq 1$, $$ T(n) = \frac{(2n)!(c/2)^n}{(2n-1)n!} \sim \frac{1}{\sqrt{2} n} \left( \frac{2c}{e} n \right)^n. $$ The first few terms (starting with $T(1)$) are $$ c,c^2,3c^3,15c^4,105c^5,\ldots $$

share|cite|improve this answer
Can you explain how did you get $2(P-cx)=P^2$ from identity 1. And, what is the intuition behind choosing this generating function? – Sayan Bandyapadhyay May 10 '14 at 17:08
For my first question, in particular I can't see why you are subtracting $cx$. As $T(0)=0$, I am getting $2P=P^2$. – Sayan Bandyapadhyay May 10 '14 at 17:51
I am subtracting $cx$ since identity (1) fails for $k = 1$, which in fact produces $0$ instead of $T(1)$. For further information, I suggest checking out the book generatingfunctionology. I'm using an exponential generating function since then $P^2$ corresponds to the convolution in (1) with the weights $\binom{k}{i}$. If identity (1) didn't have these weights, I would use ordinary generating functions. – Yuval Filmus May 11 '14 at 0:10
Ya, understood! Thanks :) – Sayan Bandyapadhyay May 11 '14 at 20:36

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.